Evaluating the effect of Die spacer on crown retention in fixed prosthesis - H. Benaz; MH. Salari (Tehran University of Medical Sciences, 1997)
Crown retention is related to its adaptation with tooth while there is always a gap between the crown and prepared tooth. Although this gap is filled with cements but the mechanical retention between axial walls and internal surfaces is decreased. Therefore, what is the relation between die spacer and crown retention? Does it affect retention? And if so, what is the best thickness of it? It has been a long time that various techniques are recommended and used to improve the adaptation of crowns. According to Fusayama and based on some other researches, it can be concluded that by using die spacer we can noticeably decrease the thickness of cement and improve the adaptation of cement. In addition, many studies on thickness and amount of die spacer concluded that by using die spacers, in %55 of cases crown retention was increased while in 30% decreased and 10-15% have not changed. Hence, it seems that using die spacer is generally beneficial and the best thickness of it according to our research is 2-4 layers that can improve retention by 41%.